Considerations in Breast Augmentation in the Adolescent Patient - Jordan, Sumanas W.; Corcoran, Julia (Seminars in Plastic Surgery, 2013)
Nearly 320,000 breast augmentations were performed in 2011, with adolescents under 18 years of age accounting for 4,830 procedures (1.5%). Breast development typically starts at 11 years (range, 8–13 years) and is complete at 15 years (range, 11–18 years). This wide age range for physical maturity matches the equally wide range of emotional maturity in this patient population. Developmental, psychological, and regulatory aspects unique to adolescent breast augmentation are reviewed. Self-image and societal influences must be considered, including both internal and external motivations for seeking breast augmentation. Preoperative assessment and counseling of these patients are discussed. Both parental consent and adolescent assent must be considered. Ideal conditions for adolescent assent are described. Breast augmentation for purely aesthetic purposes should be undertaken with extreme caution as ideal conditions for complete assent are rare. Augmentation as a technique for breast balancing in cases of significant asymmetry can be helpful.
Keywords: breast development; body image; patient selection; assent